Manager's guide to using the force : leadership lessons from a galaxy far far away. - Urick, Michael J. (Exploring Effective Leadership Practices Through Popular Culture Ser., 2021)
5: Self-sacrifice -- Servant Leadership -- Focusing on the Greater Good -- Understanding One's Role within a Context -- Role of Emotions -- Summary -- 6: Values -- Discipline -- Duties and Virtues -- Greatest Good for the Greatest Number? -- Summary -- 7: Bases of Influence -- Becoming More Influential -- Expertise and Mastery -- Summary -- 8: Communicating -- Communication and Leadership Theory -- Communicating with Confidence -- From a Certain Point of View -- Summary -- 9: Inclusivity -- Social Identity -- Types of Diversity -- Jedi and Diversity -- Summary.